2007
DOI: 10.1088/0031-9155/52/13/002
|View full text |Cite
|
Sign up to set email alerts
|

Collapsed cone convolution and analytical anisotropic algorithm dose calculations compared to VMC++ Monte Carlo simulations in clinical cases

Abstract: The purpose of this work was to study and quantify the differences in dose distributions computed with some of the newest dose calculation algorithms available in commercial planning systems. The study was done for clinical cases originally calculated with pencil beam convolution (PBC) where large density inhomogeneities were present. Three other dose algorithms were used: a pencil beam like algorithm, the anisotropic analytic algorithm (AAA), a convolution superposition algorithm, collapsed cone convolution (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 15 publications
2
61
0
Order By: Relevance
“…Studies on the performance and accuracy of the dose calculation algorithms in inhomogeneous phantoms have revealed that the type‐b algorithms are superior to the type‐a algorithms, 5 , 6 , 7 , 8 and that the Acuros XB algorithm is an accurate alternative to Monte Carlo calculations (9) . Type‐a and type‐b algorithms calculate absorbed dose to water.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on the performance and accuracy of the dose calculation algorithms in inhomogeneous phantoms have revealed that the type‐b algorithms are superior to the type‐a algorithms, 5 , 6 , 7 , 8 and that the Acuros XB algorithm is an accurate alternative to Monte Carlo calculations (9) . Type‐a and type‐b algorithms calculate absorbed dose to water.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of the algorithm on the target coverage in lung cancer treatment has been described 1 , 7 , 8 , 10 . Two recent studies have quantified the difference between AAA and Acuros XB in stereotactic body radiation therapy of non‐small cell lung cancer 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situations like this, the AAA of Eclipse has been shown to underpredict dose5, 20 and CCCS overpredict dose,21 both relative to gold standard Monte Carlo calculations. These publications are consistent with local observations whereby Mobius3D systematically calculates more dose to lung targets than Eclipse , where the reality is most likely to be somewhere in between.…”
Section: Discussionmentioning
confidence: 97%
“…Another limitation of our study was that only one Type‐A and one Type‐B algorithm were investigated; therefore, the results and trends found may or may not be generalizable to other algorithms. Herein, the Type‐B algorithm utilized was AAA, which may be less accurate than another Type‐B algorithm, CCC 24, 25, 26. However, it should also be noted that AAA is still quite prevalent in the current clinical treatment planning, which makes this study quite relatable to contemporary practice.…”
Section: Discussionmentioning
confidence: 99%